Effect of ultradispersed iron particles on carbon matrix on carp growth and development - Malenkina K.A.; Arinzhanov A.E.; Miroshnikova E.P.; Kilyakova J.V. (Ветеринария и кормление)
The use of nanoforms of microelements in feed rations today represents a current area of scientific research in the field of feeding and feed production. The article presents the results on the evaluation of the effect of ultradisperse iron particles on carbon matrix (UDP Fe-C) on productivity, morphological and biochemical indices of fish (Cyprinus carpio) blood. Three groups of fish (n=15) were formed for experimental studies: control and two experimental groups, which were additionally included Fe-C UDP at different dosages in the main diet. The UDP Fe-C was introduced into the feed after its dispersion at a frequency of 35 kHz for 30 minutes. As a result of studies lasting 56 days, it was found that feeding Fe-C UDP as part of the diet in the amount of 0.8 mg/kg of feed (Group I) leads to an increase in carp productivity by 13.3% (PЈ0.05). Analysis of morpho-biochemical blood parameters revealed in group I an increase in the number of platelets by 29.6% (PЈ0.05) and a decrease in the number of leukocytes by 10.1% (PЈ0.05), relative to control values. Feeding UDP Fe-C as part of the diet at a dose of 2 mg/kg of feed (group II) did not have a significant productive effect. At the same time, in group II, an increase in the amount of hemoglobin, erythrocytes and hematocrit was noted - by 9.9% (PЈ0.01), 16.9% (PЈ0.05) and 20.1% (PЈ0.05), respectively. A high level of iron in the blood of fish was established only at a dosage of 0.8 mg/kg of feed - 43.5% (PЈ0.01) higher than the control. Thus, the efficacy of carbon matrix iron UDP at a dosage of 0.8 mg/kg in carp feeding has been established, contributing to increased productivity and improvement of morphological and biochemical indicators of fish blood. In this regard, the results of research leave a wide scope for further research not only in the field of feeding fish, but also farm animals in general.